FILSAFAT PANCASILA DALAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Yulia Marni (STKIP Subang, 2022)
The philosophy of Pancasila, which is a national guideline in education, is used as a way of life that is believed to be true. If we link Pancasila and the education system in terms of educational philosophy, then Pancasila is the nation's view of life which animates in everyday life. The application of this is manifested in social, cultural, national and multi-ethnic life. In addition, Pancasila as values ​​that develop in religious and customary beliefs, must be instilled in education from an early age. Elementary school (SD) is one of the formal education courses that is pursued as an arena that plays a role in developing Pancasila values ​​to create a national character. The purpose of this research is to see how Pancasila philosophy is given in the education system in elementary schools in the context of character building. The method used by the author in this research is a literacy study/literature review through dissection of articles and books as reference material coupled with looking at life story studies, individual experiences, interviews, introspection and observation of visual texts. The results of the research that the authors found were that there is character education for students in elementary schools which must be based on the Pancasila philosophy. These values ​​and attitudes are reflected in three aspects, namely ontology, epistemology and axiology.